Greater Omentum Abscess Revealing an Upper Genital Infection - Romain L’Huillier; Alexandra Braillon (Diagnostics)
In this clinical case, we report an upper genital infection revealed on Computed Tomography by a greater omentum abscess. The infection was confirmed by endocervical swabs and ultrasound-guided sampling of the epiploic abscess, which found the same bacteria (Parvimonas micra). Omental absecesses are most often secondary to spontaneous or post-operative infarction of the greater omentum, and this observation provides a new cause for epiploic abscesses.